Diversity of Survival Patterns among Escherichia coli O157:H7 Genotypes Subjected to Food-Related Stress Conditions - Elhadidy, Mohamed; Álvarez-Ordóñez, Avelino (Frontiers in Microbiology, 2016)
The purpose of this study was to evaluate the resistance patterns to food-related stresses of Shiga toxin producing Escherichia coli O157:H7 strains belonging to specific genotypes. A total of 33 E. coli O157:H7 strains were exposed to 7 different stress conditions acting as potential selective pressures affecting the transmission of E. coli O157:H7 to humans through the food chain. These stress conditions included cold, oxidative, osmotic, acid, heat, freeze-thaw, and starvation stresses. The genotypes used for comparison included lineage-specific polymorphism, Shiga-toxin-encoding bacteriophage insertion sites, clade type, tir (A255T) polymorphism, Shiga toxin 2 subtype, and antiterminator Q gene allele. Bacterial resistance to different stressors was calculated by determining D-values (times required for inactivation of 90% of the bacterial population), which were then subjected to univariate and multivariate analyses. In addition, a relative stress resistance value, integrating resistance values to all tested stressors, was calculated for each bacterial strain and allowed for a ranking-type classification of E. coli O157:H7 strains according to their environmental robustness. Lineage I/II strains were found to be significantly more resistant to acid, cold, and starvation stress than lineage II strains. Similarly, tir (255T) and clade 8 encoding strains were significantly more resistant to acid, heat, cold, and starvation stress than tir (255A) and non-clade 8 strains. Principal component analysis (PCA), which allows grouping of strains with similar stress survival characteristics, separated strains of lineage I and I/II from strains of lineage II, which in general showed reduced survival abilities. Results obtained suggest that lineage I/II, tir (255T), and clade 8 strains, which have been previously reported to be more frequently associated with human disease cases, have greater multiple stress resistance than strains of other genotypes. The results from this study provide a better insight into how selective pressures encountered through the food chain may play a role in the epidemiology of STEC O157:H7 through controlling the transmission of highly adapted strains to humans.